Приборное обеспечение измерения параметров ультразвуковых воздействий в технологических процессах - Lanin, V. L.; Dezhkunov, N. V.; Tomal, V. S. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
Contact and non‑contact vibration meters have been developed for periodic and continuous monitoring of vibration amplitude in ultrasonic technological equipment. To assess the intensity of cavitation in liquid media, cavitation activity indicators and cavitometers have been designed, enabling measurement of signal levels within the range of maximum spectral density of cavitation noise. The application of the developed instruments will improve product quality, reduce defect rates, and lower equipment energy consumption by maintaining optimal technological process conditions.